The diamondback moth, Plutella xylostella (L.), (Lepidoptera: Plutellidae) and its biological control in the Eastern Cape Province, South Africa - Smith, Tamara Jane (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2003)
The diamondback moth, Plutella xylostella (L.), is a pest on crucifer crops worldwide, damaging the leaves, florets and seed pods of many crucifers including cabbage, cauliflower, broccoli and canola. It has been controlled using broad-spectrum insecticides, but this has led to a rapid build-up of insecticide resistance. In the Grahamstown area of the Eastern Cape Province, South Africa, diamondback moth showed resistance to cypermethrin (a pyrethroid) on commercially grown cabbages. Therefore it is imperative that other methods of control be adopted, including both cultural control and biological control using parasitoids, and that these are incorporated into an Integrated Pest Management (IPM) programme. The diamondback moth and its parasitoids were monitored weekly from April 1997 to November 1999 at three sites near Grahamstown. One site was a commercial farm with an active insecticide spraying program; the others were unsprayed. Infestation levels were highest during spring (September to November) and autumn (March to May). Nine species of parasitoids were associated with the diamondback moth, with abundances being highest over spring and early summer (September to December). Cotesia plutellae (Kurdjumov) dominated the sprayed site, while the unsprayed sites yielded a complex of parasitoids, including C. plutellae, Diadegma mollipla (Holmgren), Diadromus collaris Gravenhorst and Oomyzus sokolowsldi (Kurdjumov). Parasitism levels ranged between 10 and 90%. There was a large amount of site-to-site and year-to-year variation. Parasitoids were an effective mortality factor against the diamondback moth. The effects of temperature on development and mortality, and of field size and non-crop plants on the distribution of diamondback moth and its parasitoids, were investigated. The results show that high temperatures can depress pest populations, and that the size and surroundings of fields can be manipulated to improve cultural control of the diamondback moth. Suggestions for effective rPM in the Eastern Cape Province include a reduction in insecticide applications, the use of bioinsecticides, for example Bacillus thuringiensis Berliner (Bt) and the encouragement of indigenous parasitoids by planting suitable nectar sources. Cultural control methods are also important and involve removal of cabbage refuse after harvest, management of wild crucifers around cabbage fields, scouting and monitoring the moth population and determining the optimal field size to assist with control by parasitoids.
Keywords: Plutellidae; Plutellidae -- South Africa -- Eastern Cape; Insect pests -- Biological control -- South Africa -- Eastern Cape